2017
DOI: 10.1007/s10096-017-3131-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and establishment of KPC-2-producing ST11 Klebsiella pneumoniae in a general hospital in Shanghai, China

Abstract: The aim of this study was to investigate the characteristics of carbapenem-resistant Klebsiella pneumoniae (CRKP) collected during an outbreak in a Chinese teaching hospital and to provide insights into the prevention and control of nosocomial infection. We collected unique CRKP clinical isolates from 2009 to 2013. Antibiotic-resistant genes were identified by polymerase chain reaction (PCR) and sequencing. The isolates were typed using pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 22 publications
7
35
0
Order By: Relevance
“…While that case is relatively specific since the patient might be affected during the visit and hospitalization in India, which would add more complex environmental factors to confound the results. CRKP of ST11 associated with bla KPC-2 is disseminated widely across China 18,29 , which is concordant with the results of our study. These findings all suggest that the CRKP-mediated infections in our hospital result from ST11 with KPC-2-positive K. pneumoniae isolates.…”
Section: Discussionsupporting
confidence: 92%
“…While that case is relatively specific since the patient might be affected during the visit and hospitalization in India, which would add more complex environmental factors to confound the results. CRKP of ST11 associated with bla KPC-2 is disseminated widely across China 18,29 , which is concordant with the results of our study. These findings all suggest that the CRKP-mediated infections in our hospital result from ST11 with KPC-2-positive K. pneumoniae isolates.…”
Section: Discussionsupporting
confidence: 92%
“…KPC‐2 was commonly associated with multiple STs, but ST258 was the most prevalent in the United States. The IncF groups dominate in the spread of KPC‐2 and KPC‐3 in the United States and other countries, including Australia, Canada, China, Italy, Romania, and Spain Only one study has reported on IncF groups in KPC‐3 in Portugal and Romania . Few occurrences were also reported in other countries, including the United States, Mexico, and Spain.…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
“…The molecular epidemiological methods had been used for tracking and characterization of CRKP isolates by PFGE and MLST which were accepted to differentiate the species-both of which indicated that CRKP ST11 was identi ed as the predominant sequence type strain in our study. The epidemiology of CRKP is continually evolving, and now the advantage strains of bla KPC -producing K. pneumoniae ST11 have been reported, which is the most frequently detected KPC-producing K. pneumoniae clone in China [14][15][16]. Interestingly, ST11 also occupied predominant isolates according to the prepotent PFGE pattern.…”
Section: Discussionmentioning
confidence: 99%